2016
DOI: 10.1038/nature20161
|View full text |Cite
|
Sign up to set email alerts
|

Structure of photosystem II and substrate binding at room temperature

Abstract: Light-induced oxidation of water by photosystem II (PS II) in plants, algae and cyanobacteria has generated most of the dioxygen in the atmosphere. PS II, a membrane-bound multi-subunit pigment-protein complex, couples the one-electron photochemistry at the reaction center with the four-electron redox chemistry of water oxidation at the Mn4CaO5 cluster in the oxygen-evolving complex (OEC) (Fig. 1a, Extended Data Fig. 1). Under illumination, the OEC cycles through five intermediate S-states (S0 to S4)1, where S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
365
6
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(396 citation statements)
references
References 73 publications
14
365
6
3
Order By: Relevance
“…The high-resolution structures of PSII analyzed so far were for the dark-stable S1 state 4,5 , although a few studies on the low-resolution intermediate S-state structures have been reported by TR-SFX [9][10][11] . During the revision of our manuscript, Young et al reported a 2F-illuminated state structure at 2.25 Å resolution where no apparent changes around O5 were observed 12 , although estimations of the resolution could yield somewhat different values so that small movement of some water molecules may escape the detection. In order to achieve resolution high enough to uncover small structural changes induced by flash illuminations yet allowing Si-state transition to proceed efficiently, we determined the optimal crystal size of PSII with a maximum length of 100 µm, which diffracted up to a resolution of 2.1 Å by a SACLA-XFEL pulse (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high-resolution structures of PSII analyzed so far were for the dark-stable S1 state 4,5 , although a few studies on the low-resolution intermediate S-state structures have been reported by TR-SFX [9][10][11] . During the revision of our manuscript, Young et al reported a 2F-illuminated state structure at 2.25 Å resolution where no apparent changes around O5 were observed 12 , although estimations of the resolution could yield somewhat different values so that small movement of some water molecules may escape the detection. In order to achieve resolution high enough to uncover small structural changes induced by flash illuminations yet allowing Si-state transition to proceed efficiently, we determined the optimal crystal size of PSII with a maximum length of 100 µm, which diffracted up to a resolution of 2.1 Å by a SACLA-XFEL pulse (Extended Data Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Critical for the reaction is a Mn 4 CaO 5 cluster in the catalytic site of the protein, which, like many catalytic metal clusters, is highly sensitive to radiation damage. High resolution and damage-free structures from XFELs have provided new insights into how the cluster is organised 234,235 and, perhaps even more importantly, elucidated changes upon controlled flash illumination 234,236–238 . All examples for TR-SFX mentioned earlier are natively light-activated proteins.…”
Section: Applications In Structural Biologymentioning
confidence: 98%
“…DIALS has already been used to process data at X-ray freeelectron laser sources Lyubimov et al, 2016;Young et al, 2016). Future developments in DIALS will include its extension for use with other sources and methods, including electron diffraction.…”
Section: Discussionmentioning
confidence: 99%